Recommendations from SEC’s plain English handbook: Perspectives from behavioral research - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2019)
The SEC published the plain English handbook in 1998 with the objective of providing preparers of financial disclosures with a guide to using well-established techniques to create clearer and more informative disclosure documents. The handbook provides various recommendations to preparers of disclosure documents. In this study, I examine and systematically synthesize the extent behavioural research literature that investigates the impact of implementing these recommendations on investors. I do so by developing a framework to systematically examine relevant studies. Overall, the analysis provides important insights from a behavioural perspective into how and why investors react to various recommendations in the SEC’s plain English handbook. My study provides insights to investors, and other stakeholders about how/why key recommendations in the handbook can influence investor judgments. It also provides regulators with insights into how recommendations contained in the handbook are consistent with its stated objective of making disclosures more accessible and easily understandable.